From Leadership to Innovation: The Mediating Role of Job Satisfaction in a Semi-Military Organization - Basir, Abdul; Elliyana, Ela (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
This study examines how transformational leadership and organisational culture influence innovative work behaviour in semi-military defence organisations, with job satisfaction as a mediating variable. Drawing on transformational leadership theory, Denison’s cultural model, and affective-motivational perspectives, the study explores psychological mechanisms that shape innovation in highly hierarchical settings. A quantitative survey of 288 employees from a state-owned defence manufacturer in Indonesia was analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that both transformational leadership and organisational culture significantly enhance job satisfaction. Organisational culture also directly increases innovative work behaviour, whereas transformational leadership does not exert a direct effect. Instead, its influence on innovation is fully mediated by job satisfaction. Job satisfaction itself emerges as a strong predictor of innovative behaviour. These findings suggest that in rigid and hierarchical environments, innovation is more likely to arise from cultural support and positive employee experiences than from leadership behaviours alone.